Learning Application Derivative Algebraic Functions: Ethnomathematical Studies and Digital Creator Books - Rani Darmayanti; Baiduri Baiduri; Rahmad Sugianto (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
Learning mathematics has been meaningful if it is associated with real-life problems. Ethnomathematics is an activity in which mathematical concepts are related to the local "Lontong Sayur" culture that students often encounter in real life. Ethnomathematics needs to be applied to students at the high school level. It aims to make it easier for students to understand mathematical concepts, one of which is ethnomathematics based on Digital Book Creator. This study aims to create a product as a Book Creator based on the application of ethnomathematics in learning. Applications derived from algebra help teachers create conducive conditions for students to learn. The development model used in this research is the Borg and Gall development model in the research and data collection stages. Book Creator is a simple tool for creating exciting books. The validation of materials, learning media, and culture received a score of 3.58 using "good" criteria. Book Creator can be developed to understand documents more in context to understand documents from concrete to abstract and provides several menus, namely: a) Presenting user guides and brief descriptions of Book Creator; b) Business plans and concept maps; c) A summary of the material is presented in stages equipped with sample questions and quizzes containing learning videos, audiovisual sections, and aptitude tests; and d) Summarizing, presenting summary/basic learning materials.